Ethnophytotherapy Practices for Wound Healing among Populations of District Haripur, KPK, Pakistan. (14th July 2019) - Siddique, Zeeshan; Shah, Ghulam Mujtaba; Ahmed, Hiwa M.; Nisa, Sobia; Khan, Abdullah; Idrees, Muhammad; Naz, Shumaila; Waqas Hassan, Syed; Mohiuddin, Muhammad
Abstract : Wounds, burns, cuts, and scarring may cause a serious problem for human health if left untreated, and medicinal plants are identified as potentially useful for wound healing. Therefore, the study focused on ethnophytotherapy practices for wound healing from an unexplored area, Pakistan. Ethnophytotherapeutic information was collected through well-planned questionnaire and interview methods by targeting 80 informants (70 males and 10 females), in the study area. Data was analyzed through quantitative tools like use value (UV) and credibility level (CL). A total of forty wound healing plant species, belonging to twenty-nine families, were being used in forty-six recipes. Herbs constitute (35%), shrubs (30%), trees (30%), and climbers (5%) in the treatment of multiple human injuries. For remedies preparations, leaves were most frequently utilized (52%) followed by whole plant, flowers, twigs, roots, bulb, bark, rhizome, resin, oil, leaf gel, latex, gum, and creeper. The most form of herbal preparation was powder (34.7%) and poultice (32.6%), followed by decoction, bandaged and crushed, in which 40% internally and 60 % externally applied. The drugs from these plants seem to be widely used to cure wounds: Acacia modesta, Aloe barbadensis, Azadirachta indica, Ficus benghalensis, Nerium oleander, and Olea ferruginea with higher use values (0.75). Local people are still connected with ethnophytotherapies practices for curing wounds for several reasons. This ethnomedicine and the wound healing plants are under severe threats; thus conservation must be considered. Further research should be directed towards implementing pharmacological activity on these invaluable botanical drugs.